A case of a huge mandibular tumor composed of ameloblastoma and high-grade sarcoma. Issue 5 (September 2019) - Fujita, Yusei; Tamura, Hiromi; Okunaga, Shusuke; Hamada, Masakazu; Wakabayashi, Ken; Ando, Hiroka; Adachi, Shiro; Sumi, Tetsuro
Abstract: Ameloblastoma is a benign odontogenic tumor of the jaw. Sarcoma is a rare neoplasm that accounts for only about 1% of all tumors. Here, we report a quite rare case of simultaneous occurrence of an ameloblastoma and a high-grade sarcoma in the mandible of a 65-year-old man. He was referred to our hospital because of his difficulties in eating and drinking due to a remarkable swelling of the right mandible. He had first noticed the swelling about six years before and consulted a clinic one year before, but he had refused any examination or treatment. He underwent an incisional biopsy, and it revealed a high-grade spindle cell sarcoma with massive necrosis. Therefore, we suggested surgery, but he had never hoped any operation. His poor nutritional status gradually further declined, and he died due to massive hemorrhage from the tumor. In the autopsy, the histological findings revealed that the tumor was predominantly composed of high-grade spindle cell sarcoma and contained a small amount of epithelial component which was a granular cell variant of ameloblastoma. Metastatic tumors were seen in the bilateral lungs and the liver. They contained only the sarcomatous element.